A combined calorimetric, spectroscopic and molecular dynamic simulation study on the inclusion complexation of (E)-piceatannol with hydroxypropyl-β-cyclodextrin in various alcohol + water cosolvents. (May 2019) - Cai, Chang; Liu, Min; Yan, Hui; Zhao, Yanna; Shi, Yabo; Guo, Qingying; Pei, Wenxin; Han, Jun; Wang, Zhengping
Graphical abstract: Highlights: (E)-Piceatannol (PIC) could form 1:1 stoichiometry inclusion complexes with HP-β-CD in various alcohol-water cosolvents. Negative enthalpy and entropy changes suggested that the association of PIC with HP-β-CD was enthalpy–driven process. The concentration, carbon chain length, and the number of hydroxyl groups of the alcohols affected the inclusion process. Fluorescence intensity of PIC increased with the increasing concentration of HP-β-CD and showed a slight hypsochromic shift. The microscopic structure of the inclusion complex in different alcoholic cosolvents was obtained from the MD simulations. Abstract: (E)-Piceatannol, a naturally occurring polyphenol, has gained increasing interests in pharmaceutical and food industries due to the health-promoting effects. However, the application of (E)-piceatannol is severely limited by its low solubility and poor bioavailability. Cosolvation and complexation are two effective methods to increase the solubility of insoluble active compounds. The effect of alcohol + water cosolvents on the inclusion complexation of (E)-piceatannol with hydroxypropyl-β-cyclodextrin (HP-β-CD) was investigated using isothermal titration calorimetry, fluorescence spectroscopy and molecular dynamics simulation. The stoichiometry and thermodynamic parameters for the complexation process were obtained. The results showed a 1:1 stoichiometry between (E)-piceatannol and HP-β-CD. The complexation constants decreased with the increase of the alcohol concentration and the alkyl chain length, but increased with the increasing number of hydroxyl groups of the alcohols. The main driving forces for the inclusion process were obtained from the enthalpy and entropy changes. The effect of temperature on the inclusion complexation was discussed in terms of the heat capacity change calculated from the temperature dependence of enthalpy change. The differences in thermodynamic parameters in different cosolvents were explained in detail based on the assumption that the alcohol acts both as a solvent and as a competitor to (E)-piceatannol. Both binding enthalpy and binding entropy exhibited a noticeable temperature dependence with almost complete enthalpy–entropy compensation. Fluorescence intensity of (E)-piceatannol increased with the increasing concentration of HP-β-CD and showed a slight hypsochromic shift. The microscopic structure of the inclusion complex in different alcoholic cosolvents was obtained from the molecular dynamics simulation. These results illustrated the importance of optimizing the solvent systems when utilizing cyclodextrins as food or drug carriers.